The Effectiveness Of Visual Research In Enhancing The Cultural Knowledge And Practices In Creative Industry - Rafee, Y.M; Doris, Anak Maying; Sarah Naemah, Aman Leong; Awang Hamdan, Awang Arshad; Siri, H.; Sylvester Wielding, Anak Jussem; Abol Hassan, M.Z; Halim, Hakimi; Bala, P. (Universiti Malaysia Sarawak, 2019)
This paper aims to explain the effectiveness of visual research to investigate cultural objects as the way to enhance cultural knowledge and practices in the creative industry. Based on the experiential study that was participated by the researcher, has discovered the factors that influenced the effectiveness in visual research based on the three different case studies which particularly on the cultural heritage of Parang Bajau at Kg. Siasai, Kota Belud, Ring Ladies of Embhan Community at Padawan, Sarawak, and Megalith Cultures of Kelabit Highlands at Bario, Miri. Through the comparisons based on the three case studies has identified three factors of visual research which is internal, external and the context of the research subject. These factors will contribute for better documentation, especially in visual, particularly for practicing researcher in the cultural studies, enhancing the information of cultural knowledge, developing the creative economy through the representation of visual cultures and most significant for the society purposes that own the culture.